Turkish nationwide survEy of glycemic and other Metabolic parameters of patients with Diabetes mellitus (TEMD study). (December 2018) - ,; Guldiken, Sibel; Ayturk, Semra; Yilmaz, Murat; Asik, Mehmet; Dinccag, Nevin; Cakmak, Ramazan; Turker, Fulya; Idiz, Cemile; Hacisahinogullari, Hulya; Bagdemir, Elif; Yildiz, Busra; et al.
Abstract: Aims: Turkey has the highest prevalence of diabetes in Europe. It is therefore essential to know the overall cardiovascular risk and reveal the predictors of metabolic control in Turkish adults with diabetes mellitus. Methods: A nationwide, multicenter survey consecutively enrolled patients who were under follow up for at least a year. Optimal control was defined as HbA1c < 7%, home arterial blood pressure (ABP) < 135/85 mmHg, or LDL-C < 100 mg/dL. Achieving all parameters indicated triple metabolic control. Results: HbA1c levels of patients (n = 5211) were 8.6 ± 1.9% (71 ± 22 mmol/mol) and 7.7 ± 1.7% (61 ± 19 mmol/mol), in Type 1 and Type 2 diabetes, respectively. Glycemic control was achieved in 15.3% and 40.2%, and triple metabolic control was achieved in 5.5% and 10.1%, respectively. Only 1.5% of patients met all the criteria of being non-obese, non-smoker, exercising, and under triple metabolic control. Low education level was a significant predictor of poor glycemic control in both groups. Conclusions: Few patients with Type 2, and even fewer with Type 1 diabetes have optimal metabolic control in Turkey. TEMD study will provide evidence-based information to policy makers to focus more on the quality and sustainability of diabetes care in order to reduce the national burden of the disease.